The influence of hospital type (public versus private) on mortality and survival after stroke - Moro, Carla Heloisa Cabral; Mendes, Maria Izabel Rodrigues; Wiggers, Milena Veiga; Cardoso, Thaís de Faria; Diegoli, Henrique; Pinto, Luciano Henrique; Lima, Helbert do Nascimento (Arquivos de Neuro-Psiquiatria, 2025)
Stroke has been a leading cause of death in Brazil throughout the past three decades. Although several cities in the country have implemented urgent/emergency stroke care units, the impact of the hospital type (public versus private) has not been evaluated.To compare the mortality and survival of patients admitted with stroke to two private hospitals without stroke units with a public hospital with a stroke unit.We conducted a historical cohort in the city of Joinville, Southern Brazil. Stroke patients admitted to a public hospital with a stroke unit were compared with those admitted to private hospitals without stroke units in terms of fatality rate and 30-day survival between January 2018 and December 2020. The Cox regression was used.Of the 4,508 patients, 85.6% were from public hospital, and 14.4%, from the 2 private hospitals. The crude mortality rate was of 11.4% among the public hospital patients, and of 9.1% among the patients from the private hospitals (p = 0.085). In the multivariate analysis, there was no difference in mortality between patients treated in the public hospital with a stroke unit (hazard ratio = 1.21; 95%CI: 0.87–1.68; p = 0.262) and those admitted to the 2 private hospitals without a stroke unit.Stroke units are an important public policy that minimizes the impact of stroke.
Keywords: Stroke; Survival Analysis; Health Care Economics and Organizations